The role of women in the process of buying white goods and an application for Kazakhstan - Myrzabekkyzy, K.; Bolganbayev, A.; Kelesbayev, D. (Journal of Economic Research & Business Administration, 2021)
The main purpose of this study is to determine the role of Kazakh women in the purchase process of white goods. We also aimed to reveal the role distribution inside the family. Moreover, we tried to determine the demographic and socio-economic variables that affect the role of women in the decisionmaking process of purchase decisions. Because of the rapidly changing economic conditions and intense competitive environment in Kazakhstan requires businesses to carefully perform customer analyses for a more successful marketing. Therefore, this study investigates the role of women in the purchase process of white goods in northern Kazakhstan (North, South, East and West). For this, we conscripted 396 Kazakh women living in Northern, Southern, Eastern and Western Kazakhstan and gave questionnaires to them. Primary data is collected via questionnaires using a proven scale and we used methods such as Cronbach’s Alpha Coefficient, Confirmatory Factor Analysis (CFA), and Structural Equivalency Model (SEM) in order to evaluate the results. Key words: purchase, purchase process, purchase decisions, decision-making process, white goods, women’s role.